Dietary practices and motivations of selected Filipino vegetarians - Sayoc, Juliette P.; Chua, Consuelo T. (2009.)
This study explored the dietary practices and motivations of selected Filipino vegetarians. Specifically, it looked into the self-identified reasons and motivations for adopting a vegetarian diet, the advantages and disadvantages of vegetarianism, and the dietary pattern and food preferences of Filipino vegetarians. The study also examined the responses of family members to the dietary change of the vegetarian and the vegetarian's influence in family meal management. Fifteen Filipino vegetarians were purposely chosen and surveyed using open-ended questionnaires. The age of the respondents ranged from twenty (20) to forty-two (42) years old. The classifications of the vegetarians included: strict vegans, lacto, lactovo, pesco and pesco-lacto-ovo vegetarians. The data gathered were analyzed using content analyzed using content analysis and descriptive statistics. Results revealed the personal stands, attitudes, beliefs and taboos that motivated respondents to adopt a vegetarian diet. Motivations that were observed include: ethical animal treatment, environmental concerns, health problems, significant personal experiences, social influences and spiritual beliefs. The shift to a vegetarian diet resulted to several advantages for the Filipino vegetarians when it comes to health, lifestyle, economy and attitude. However, vegetarians also encountered difficulties such as dining inconveniences, social discrimination and food palatability. The typical diet of the vegetarian respondents consists of staples such as grains, vegetables, legumes and fruits; meat substitutes such as mock meats, tofu and texturized vegetable protein (TVP) and vegetarian snacks such as vegetarian pastries and soy ice cream. In reference to their families, the dietary change of the vegetarian posed different responses from the family members. Some families were supportive; others were unsupportive, while a few families remained oblivious. In most cases, the vegetarian respondents were the sole vegetarian in the family. Although this is the case, the vegetarians have influenced family meal management specifically in terms of menu planning, food preparation, purchasing, food consumption and dining outside home. Recommendations were provided for the different stakeholders of the study: vegetarians, researchers, nutritionists, entrepreneurs, policy-makers and home economists.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Vegetarians -- Philippines